Perception of Basic Safety Training Using Analysis Gap - et al., Darul Prayogo (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Until now, official schools tend to have a rigid, hard, military, seniority, identical work in government and do not display the academic side. This article was created to provide an overview of the gap between desire and reality that includes academic, food and boarding conditions, especially in Semarang Shipping Polytechnic.The expectation of cadets for all variables does not reach 100%, meaning that there is a gap between the cadets' expectations of their academic, aramaic and food perceptions. A lower value means a higher gap, it can be concluded that the availability of supporting equipment (hours, remote air conditioners, markers, erasers, etc.), the hostel has adequate facilities, orderly and safe. Does not meet the expectations of cadets, as well as eating menu and its variations do not meet Taruna hopes.This happens because the number of cadets exceeds the capacity of the dormitory and the need for renovations because the building is more than 34 years old, and there is still intimidation from seniors so that cadets feel uncomfortable in the classroom or dormitory.